The assessment of environmental flow status in Southeast Asian Rivers: a review - Hairan, Mohammad Haroon; Jamil, Nor Rohaizah; Looi, Ley Juen; Azmai, Mohammad Noor Amal (Elsevier BV, 2021)
Southeast Asia (SEA) is a socio-economically and environmentally dynamic region of the world, with abundant renewable freshwater resources. At the same time, the population of the region is increasing and leading towards unsustainable water use and strict water management. The overall environmental flow status of Southeast Asian Rivers is assessed in this study, which is based on a critical review of the available literature of some important river basins of the study area. The results show that all riparian countries of the Mekong River are trying to utilize the hydropower potential of the river where more than 12,000 dams are constructed, which leads to significant alteration of hydrological regime in all tributaries of MRB. The two influential countries China and India are sharing the Brahmaputra River, where both countries are planning to construct dams. The 400 planned dams on this river will make the area the most concentrated region of the world in terms of big dam construction, while the low lying areas in India and Bangladesh are posing the threat of nutrient pollution due to excessive agricultural activities. The Citarum River in Indonesia is suffering from overburden of pollution, which makes the river heavily polluted while the Muda river in Malaysia is facing a lack of Integrated Water Resources Management (IWRM) and lack of stakeholders’ engagement. Moreover, many of river basins in rest of SEA countries i.e. Lao PDR, Cambodia, Viet Nam, Myanmar, Philippines, Brunei Darussalam, and East Timor are lacking attention to research and policy to this field, therefore, the status of Environmental Flow is ranked unsatisfactory in most river basins of SEA.